APPLICATION OF THE SELF-DIRECTED LEARNING (SDL) LEARNING MODEL IN ENVIRONMENTAL ENGINEERING COURSES FOR STUDENTS OF THE BUILDING ENGINEERING EDUCATION STUDY PROGRAM, UNIVERSITY OF PALANGKA RAYA, ACADEMIC YEAR 2020/2021 - Tarita Aprilani Sitinjak; Lola Cassiophea; Ni Putu Diah Agustin Permanasuri; Artike Telaumbanua; Alen Setiawan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Teachers must work on learning assignments from home (continuously and as a controlled routine) on an ongoing basis and have the potential to be unproductive to work in a completely new environment and without the supervision of a leader (intense). However, there are a number of ways to deal with this problem, especially preventing teachers from being confused in applying appropriate and effective learning models, as well as continuous professional development, they definitely want to be productive in utilizing their time during the Covid 19 pandemic. Time management must be carried out and controlled properly to improve quality. teacher professionalism as a professional educator. The solution, teaching staff is required to be able to design learning media as an innovation by utilizing online media (online). This research is motivated by the learning outcomes of Building Engineering Education students who program Environmental Engineering Courses are still relatively low below a score of 60 (C value). Self-Directed Learning (SDL) is learning in which the conceptualization, design, implementation and evaluation of learning projects are directed by students. The key point is whether students choose to concentrate on learning. This type of research is classroom action research which is carried out online, this is due to the ongoing covid-19 pandemic. Quantitative data in the form of numbers or scores obtained from student learning outcomes tests. The instrument used in this research is the final test of student learning outcomes. The parameters in this study are the learning outcomes and independence of Building Engineering Education students in the Environmental Engineering course. Plans or targets will be published in the Balanga Journal.